Optimal Reserve Level of Central Bank and Foreign Investment: An Analytical Study - Hamzh, Hasan Kareem; Shakir, Hassan; Almershedy, Hayder Jawed; Alktrani, Sundus Hameed (International Journal of Psychosocial Rehabilitation, 2020)
Most countries in the world, especially developing countries, pool their foreign exchange reserves to ensure that their balance of payments imbalances can be easily addressed, defend their national currency exchange rate, and meet their obligations to their creditors. It also represents a barrier against tragic economic and financial conditions. A key factor to win the confidence of creditors provides a safer environment to attract investors, both domestic and foreign. There is no difference in views on the conditions of building reserves at safe levels and their optimal size and avoiding excessive retention through reduced exposure opportunities and increased cost of opportunity to retain them. The research was to show the reserve cycle in Iraq during the period (2004-2017) a number of indicators at the optimum level, especially the Hener equation (in addition to other indicators such as import coverage, broad money supply, internal and external indebtedness, Iraq has proved to maintain a higher-level optimum. Therefore, it has been predicted that if IFAD invests in the Sovereign Wealth Fund and in the form of an investment company with key elements in its creation, the Fund will contribute to the diversification of Iraq's income sources as well as participation in development. Solutions to the growing problems of the Iraqi economy.